Clinical features and laboratory indicators of dengue infection in China: a retrospective study of adult patients in a hospital of traditional Chinese medicine - Nie, Qilong; Li, Mingyang; Liang, Qiuyan; Ren, Jian; Li, Tong; Peng, Wenya; Luo, Cuifen; Mo, Xiaoai; Ma, Xiaojun; Li, Jianhong; Jiang, Kaiping (Frontiers in Medicine, 2025)
BackgroundDengue is an arboviral disease caused by the dengue virus, primarily transmitted by mosquitoes in tropical and subtropical regions. Despite preventive measures, the incidence and mortality of dengue remain significant. While the acute phase of infection often presents with mild, self-limiting symptoms and may mimic other undifferentiated febrile illnesses, the risk of mortality is particularly high during the acute phase of secondary infections, which are associated with more severe clinical manifestations. Liver dysfunction has been strongly linked to the severity of the disease, and it plays a critical role in determining patient outcomes.MethodsThis retrospective observational study was conducted at Foshan Hospital of Traditional Chinese Medicine, including 533 hospitalized dengue patients diagnosed between June and December 2024. Clinical symptoms (e.g., fatigue, headache, muscle pain, dry mouth, rash, nausea) and laboratory parameters (e.g., complete blood count, liver function tests, lactate dehydrogenase, C-reactive protein, procalcitonin) were collected. Patients were categorized into three groups based on liver function test results: non-liver injury (ALT ≤ 40 U/L, AST ≤ 40 U/L), mild liver injury (ALT or AST levels between 40 U/L and 80 U/L), and severe liver injury (ALT > 80 U/L or AST > 80 U/L).ResultsAmong the 533 patients, 48.03% were male and 51.97% were female, with the majority (61.35%) in the 51–80 years age range. Common clinical symptoms included fatigue (92.50%), poor appetite (90.99%), dry mouth (62.66%), and headache (52.53%). Significant laboratory abnormalities included leukopenia (63.41%), thrombocytopenia (80.11%), and elevated liver enzymes (AST 84.99%, ALT 52.53%). Stratification based on liver injury severity showed that the severe liver injury group had significantly higher levels of inflammatory markers (CRP, PCT), and tissue damage markers (LDH, CK) compared to the non-liver injury and mild liver injury groups. The severe liver injury group also had a younger median age compared to the other two groups (p < 0.05). Additionally, bone joint pain and melena were more frequently observed in the severe liver injury group, highlighting their association with liver injury severity.ConclusionDengue patients commonly present with symptoms such as fatigue, poor appetite, and dry mouth, with laboratory abnormalities including leukopenia, thrombocytopenia, and elevated liver enzymes.